Exploring Traces of Equity in Teachers’ Instructional Practices, Assessment and Treatment with Students in Early Years of Education - Muhammad Uzair-ul-Hassan, Iram Parveen (JECCE, 2023)
Culturing equitable practices in learners’ early years of education are significant for their sound development and upbringing. According to OECD (2012), the education systems are highest in performance when quality and equity exist in them. The extent to which schools are equitable depends upon the learners how the learners perceive education as equitable. Most recently, Pakistan’s global commitment to achieve Sustainable Development Goals (SDGs) compelled policy developers and researchers to address equity issues of early childhood education in Pakistan. For the study, the researchers collected evidences from students of grade-level three of public schools in Punjab pertaining to their experience of equity in teachers’ instructional practices, assessment and treatment. Convergent mixed-methods design was used for the study. Data were collected from teachers, head teachers, students and parents were major stakeholders. Teachers teaching students of early years of education were randomly selected. For quantitative data, 2023 teachers responded on the questionnaires, while, for qualitative data, interviews were conducted from 20 head teachers, parents and students. We concluded that students have had fewer equitable experiences at schools. Mostly, teachers had been inequitable in their instructional practices, treatment, and assessment in early years of education. It was recommended for schools to address inequitable situation particularly in terms of teachers’ treatment, assessment and instructional practices during early years of students’ education